The Effectiveness of the Implementation of Electronic Land Registration at the Office of National Land Agency - Nabila Chyntia Dahani (Sultan Agung Notary Law Review, 2022)
The purpose of this research is to analyze: 1) Implementation of electronic land registration at the Office of the National Land Agency of Sragen Regency. 2). The effectiveness of the implementation of electronic land registration at the Office of the National Land Agency of Sragen Regency. The approach method used in discussing this research problem is a sociological juridical approach. The research specifications used are descriptive analytical research. This type of data uses primary data and secondary data. The data analysis method used in this research is descriptive qualitative. The results of the study concluded: 1) The implementation of electronic land registration at the Office of the National Land Agency of Sragen Regency can guarantee legal certainty, because electronic certificates are guaranteed by law and can be used as legal evidence. Registration of this electronic certificate can be through PPAT assistance through the site https://loket.atrbpn.go.id. After the service registration and documents have been uploaded, the land office will later validate the applicant's files online. If the verification is smooth, a deposit order will be printed and the Applicant needs to make payments according to the applicable rules. After making the payment, the file will be processed immediately. The collection is done by coming to the BPN Office of Sragen Regency according to the specified schedule. 2). The effectiveness of electronic land registration at the National Land Agency Office of Sragen Regency is more effective than conventional land registration. This is because the implementation of land registration online or electronically provides many benefits to the community.